PSI-30 Identification of fetal microchimerism in older ewes using qPCR. (5th December 2019) - Teague, Hannah M; Niland, Erika S; Pierce, Natalie L; Taylor, J Bret; Brown, J Alison
Abstract: The presence of a male co-twin during pregnancy has been found to impact lifetime reproductive performance in the sibling ewe. XY chimerism, thought to originate from a male co-twin, has been observed in ewes, and may be associated with the rare development of freemartins. Fetal ram DNA has been observed in the maternal circulation during pregnancy, but it is unknown if this chimerism persists after parturition. The objective of this study was to determine if fetal male cells were present in soft tissues of older ewes and if so, does the occurrence differ with lifetime offspring sex ratio. Eight ewes approximately 7-years-old and having given birth to at least 71% female (n = 4) or 82% males (n = 4) were tested. DNA was extracted from 10 different tissues from each ewe (n = 80). In triplicate, real-time PCR (qPCR) was used to identify the presence of the SRY gene in each sample. Using the SRY primer pair, male DNA was identified in the brain (between 1.25 ng / µL and 125 pg / µL) and liver (between 125 and 12.5 pg / µL) from a ewe that had given birth to two males during her lifetime. If any additional male fetal DNA was present, it was below the detectable limits. In addition to giving birth to two males, this ewe was also born with two male co-siblings, thus the origin (sibling or offspring) of the male DNA is not known. These data suggest fetal cell transfer in sheep is possible and the frequency of fetal microchimerism is not associated with sex ratio of lifetime offspring.